Sistem Pendukung Keputusan Pemilihan Skincare Menggunakan Metode Weighted Product Berbasis Web - Samsinar Z. Moga; Heru Prabowo; Priscilla Gabriel (Jurnal Elektronik Sistem Informasi dan Komputer, 2025)
Having healthy face skin is everyone's desire. Everyone can have healthy face skin by using facial wash, moisturizer, and sunscreen with ingredients that are safe and suitable for each type of face skin. However, not suitable skincare product can cause allergies, red rashes, stinging, itching, and even chronic skin inflammation. To address this issue, this research developed a decision support system application that can provide skincare recommendations to each skin type. This research is quantitative. Data was collected through observation, questionnaires, and literature review. This research use waterfall method with PHP programming language and MySQL database. The testing methods used are black box testing and beta testing. From the results of data and system processing, skincare recommendations for each type of face skin are obtained. This application can be developed by adding other types of skincare such as serums, toners, and so on.